Estrategias didácticas y su efectividad en el PEA de EESS en los estudiantes de séptimo año de EGB de la Escuela Manuel Wolf Herrera cantón San Jacinto de Yaguachi Provincia Guayas 2022 - Párraga Puco, Joyce Gabriela (2022)
In the present investigative work, an analysis of the effectiveness of the pedagogical strategies in the PEA of the seventh EGB students of the Esc. Manuel Wolf Herrera, belonging to the Yaguachi canton of the province of Guayas in the period 2022, was carried out. This analysis is based on the curricular contents that correspond to the area of Social Studies, the same ones that were evaluated and interpreted. In turn, a proposal was implemented that is consistent with the contents of this school level. This is how activities were designed that involve the application of information technologies, for the construction of innovative learning and that motivates students to continue in this academic process. ICTs in education have a great impact on the communicative interaction between teachers and students, which is why this proposal was created for academic purposes that contribute to the reforms in terms of microcurricular planning that each teacher prepares at the beginning of the year. . The projections made for this project will be executable for the period 2022 - 2023 of this educational institution